Construction innovation and process improvement - Akintoye, Akintola; Goulding, Jack.; Zawdie, Girma, 1946- (Chichester, West Sussex, U.K. : Wiley-Blackwell, 2012)
'This book sets out the innovative practices that have been introduced from other industries and shows how the construction industry has learn from these. It explores the commercial significance of innovation; outlines its role in transforming practice and improving competitiveness; and lists technological and market forces driving the innovation process. The authors explain why some attempts at innovation in construction fail and others succeed and detail the management of change, outlining economic, technical and organisational characteristics which may inhibit change in practice as well as examine management strategies for making change happen'--
Includes bibliographical references and index.
Keywords: Construction industry -- Technological innovations; Civil engineering -- Technological innovations; Competition; TECHNOLOGY & ENGINEERING / Civil / General